(untitled) (Research, Society and Development, 2021)
Introduction: The elderly public is at greater risk of developing nutritional deficits, since there is an impairment of physiological function. Objective: to evaluate the association between the prescribed versus infused enteral diet and the clinical outcome of elderly patients admitted to an Intensive Care Unit. Methodology: The study was sectional, developed with elderly in Intensive Care Unit of the Hospital Universitário Lauro Wanderley da Paraíba, where they were evaluated through a nutritional monitoring form. Statistical analysis used Chi-square tests assuming a significance level (p<0.05). Results: Seventy-nine elderly patients were evaluated, being the majority female with 62%, and mean age of 72.5 years. As for therapy complications, open nasogastric tube was significantly associated with unsatisfactory infused versus prescribed volume. Patients whose prescribed versus infused volume was satisfactory were hospitalized for more than 21 days. A total of 29 patients were discharged from the hospital, 69% of whom received satisfactory prescribed versus infused volume. On the other hand, 21 of these individuals had 63.6% of the total deaths that were associated with non-compliance with this variable. Conclusion: It was observed that patients who stayed more days in the ICU had a higher volume of infused diet reaching their recommended goals, in virtue of those who were discharged, noting that the majority satisfactorily received prescribed versus infused volume, since quality in nutritional therapy is needed more broadly in the elderly population.